Pelatihan Pemanfaatan Larutan Fenol Organik dalam Pakan untuk Meningkatkan Produktifitas Ternak Puyuh - Danang Priyambodo; Gilang Ayuningtyas; Fitriani Eka Puji Lestari; Fariz Am Kurniawan; Henry Kasman Hadi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
One of the impacts of the Covid 19 pandemic is many people lose their jobs. Providing quail breeding training is one solution to getting a new job or business. Quail is a small poultry that can be raised in an urban area. However, the quail manure needs to be handled properly to prevent environmental problems. One of the solutions is to utilize organic phenolic compounds made from coconut waste, mixed in quail feed. Organic phenol solution is an innovation with the function of one of which is to improve the performance of quails. The feed nutrients consumed by quails can be absorbed more completely by using liquid organic phenol so that the odor from the waste produced will also be reduced and quail production performance can be optimal. The method used is the presentation of training materials, discussions, filling out surveys, as well as participatory activities from participants through direct practice of quail cultivation. After this training, there is an increase in public insight into handling waste from quail farming, as well as an increasing desire of the community to do quail farming. It can become a source of income or new jobs for the people of Cihideung Udik Village.